2008
DOI: 10.1096/fj.08-108308
|View full text |Cite
|
Sign up to set email alerts
|

Integration of reporter transgenes intoSchistosoma mansonichromosomes mediated by pseudotyped murine leukemia virus

Abstract: The recent release of draft genome sequences of two of the major human schistosomes has underscored the pressing need to develop functional genomics approaches for these significant pathogens. The sequence information also makes feasible genome-scale investigation of transgene integration into schistosome chromosomes. Retrovirus-mediated transduction offers a means to establish transgenic lines of schistosomes, to elucidate schistosome gene function and expression, and to advance functional genomics approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 58 publications
2
90
0
Order By: Relevance
“…We have previously demonstrated that replication-incompetent Moloney murine leukaemia virus (MMLV) virions pseudotyped with vesicular stomatitis virus glycoprotein (VSVG) were capable of transducing schistosomes and integrating into the schistosome genome [18,19]. After exposure of schistosomes to virions, harvested from producer cell cultures, immunofluorescence studies indicated that the VSVG envelope on the pseudotyped virions interacted with the schistosome surface after which the retroviral capsid and RNA genome was released within the surface cells [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that replication-incompetent Moloney murine leukaemia virus (MMLV) virions pseudotyped with vesicular stomatitis virus glycoprotein (VSVG) were capable of transducing schistosomes and integrating into the schistosome genome [18,19]. After exposure of schistosomes to virions, harvested from producer cell cultures, immunofluorescence studies indicated that the VSVG envelope on the pseudotyped virions interacted with the schistosome surface after which the retroviral capsid and RNA genome was released within the surface cells [18].…”
Section: Resultsmentioning
confidence: 99%
“…The schistosome lifecycle was maintained in our laboratory by passaging through BALB/c mice as previously described [20]. Adult schistosomes, perfused from mice 49 days after infection with cercariae, were cultured at 37°C and 5% CO 2 in DMEM (Gibco), supplemented with 10% foetal bovine serum, 100 U penicillin and streptomycin, and small quantities of washed mouse erythrocytes, 2 ll washed erythrocytes (50% packed red cells)/ml culture medium, before and after exposure to virus [19].…”
Section: Parasitesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative method, researchers are beginning to use vector-based delivery of short hairpin RNAs (shRNAs), which in principle has the potential to deliver more sustained RNAi silencing in vivo. This technology builds on recent advances in the use of retroviral promoters for schistosome transgenesis (Kines et al 2008) and was recently adapted to RNAi silencing in S. mansoni with promising results (Tchoubrieva et al 2010). Additionally, in vivo gene silencing may be performed directly in the infected mouse by systemic intravenous delivery of parasite-specific siRNAs or morpholinos.…”
Section: Complications With Heterologous Expression Of Gpcrsmentioning
confidence: 99%
“…Both Cathepsins B and D have been successfully targeted by RNAi in S. mansoni leading to reduced parasite growth in culture [43,44] and resulted in a fatal phenotype when parasites were returned to the mammalian host [44]. It is anticipated that transgenic schistosomes may be available in the near future especially in light of the recent publications presenting the integration of exogenous reporter genes into the S. mansoni genome [42,83], which may further facilitate drug discovery and testing.…”
Section: Validation Of Putative Drug Targets or Resistance Mechanismsmentioning
confidence: 99%